Prevention of Knot Slippage with the Use of Cyanoacrylate Glue: A Mechanical Study. (April 2013) - Smith, George H; McEachan, JE; McLean, A; Huntley, JS
Purpose: To assess the effect of cyanoacrylate glue on knot slippage and strength in vitro . Methods: Ethibond 3/0 was tested using a tensile tester. A single drop of cyanoacrylate glue was applied to the knots. Seven knot configurations (10 samples each) were tested: (1) a surgeon's knot (S) plus 4 square throws (+4) without glue (control group), (2) S plus one square throw (+1) without glue, (3) S+1 with glue, (4) S with glue, (5) S+1 wet post-tie without glue, (6) S+1 wet pre-tie without glue, and (7) S+1 wet pre-tie with glue. Wet sutures were immersed in normal saline for 24 hours prior to knot tying. Wet pre- and post-tie sutures were immersed for one minute prior to knot tying and tensile testing, respectively. Outcome measures were the mode of failure (knot slippage or suture snapping) and the ultimate tensile strength. Results: All knots without glue failed owing to knot slippage, except for the controls, whereas all knots with glue failed owing to suture snapping. The ultimate tensile strength was significantly higher in knots with glue and controls than in knots without glue. The ultimate tensile strength did not differ significantly between S+4 without glue and S with glue (p=0.48), indicating that glue could reinforce knots and reduce the number of throws needed. Wet suture is protective against failure (p<0.01). Conclusion: Cyanocrylate glue may have clinical applications for flexor tendon repairs for which a reduced knot size is advantageous.